Chemical composition controls the decomposition of organic amendments and influences the microbial community structure in agricultural soils. Issue 4 (25th June 2021) - Heikkinen, Jaakko; Ketoja, Elise; Seppänen, Leena; Luostarinen, Sari; Fritze, Hannu; Pennanen, Taina; Peltoniemi, Krista; Velmala, Sannakajsa; Hanajik, Peter; Regina, Kristiina
Abstract: We assessed the soil carbon sequestration potential of various organic amendments of agricultural, municipal and industrial origin and the applicability of a soil carbon model to simulate it. The chemical composition of a large number of plant residues, manures, composts, digestates and biochars was determined and selected materials were incubated in soil to assess their decomposition rates and effects on soil microbial community structure. Decomposability was strongly correlated with the initial chemical composition determined by water, ethanol and acid extraction. Fresh plant materials decomposed the fastest, roots decomposed more slowly than aboveground biomass and processing decreased the decomposability of the materials. Soil carbon model Yasso07 predicted the decomposition of the amendments relatively well, except for fresh plant litter and fiber sludge from the pulp and paper industry which decomposed considerably faster than predicted by the model. Differences in the studied materials were also reflected in the soil microbial and fungal community composition. Plant root addition to laboratory microcosms induced a different soil microbial community compared to organic materials originating from the forest industry. Typical application rates of the studied amendments result in carbon sequestration at a rate sufficient to reach the goal of the 4/1000 initiative. The results can be used to select the most efficient measures to sequester carbon in croplands and to report the effects of practices like cover crop cultivation or organic matter addition.